Preoperative 18F-FDG PET/CT in Pheochromocytomas and Paragangliomas Allows for Precision Surgery. Issue 4 (April 2019) - Nockel, Pavel; El Lakis, Mustapha; Gaitanidis, Apostolos; Merkel, Roxanne; Patel, Dhaval; Nilubol, Naris; Prodanov, Tamara; Pacak, Karel; Kebebew, Electron
Abstract : Background: Fluorodeoxyglucose ( 18 F-FDG) positron emission tomography/computed tomography (PET/CT) imaging is recommended in patients with metastatic pheochromocytoma (PC) and paraganglioma (PGL). There are no data on whether routine preoperative 18 F-FDG PET/CT in all patients with PC/PGL impacts surgical management. Objective: The aim of this study was to determine whether routine preoperative 18 F-FDG PET/CT imaging affects the surgical management of patients with PC/PGLs. Methods: We analyzed clinical, biochemical, genetic, and anatomic imaging data in 93 consecutive patients with PC/PGL who collectively underwent a total of 100 operations and who had preoperative 18 F-FDG PET/CT imaging. Results: Of 100 operations, preoperative 18 F-FDG PET/CT showed additional lesions compared to anatomic imaging in 15 cases. These patients were more likely to undergo an open surgical approach ( P < 0.05). Presence of genetic mutation, redo operations, sex, age, or tumor size had no significant association with finding additional lesions on 18 F-FDG PET/CT. Conclusions: Additional lesions detected on preoperative 18 F-FDG-PET/CT imaging have an impact on the surgical approach in patients with PC/PGLs. Therefore, surgeons should routinely obtain 18 F-FDG-PET/CT imaging in patients with PC/PGL to allow for a more precise surgical intervention.